Introduction of universal infant hepatitis B immunisation in the UK- paving the way to elimination - Sema Mandal (Taylor & Francis Group, 2019)
In May 2016, the World Health Assembly ratified the first ever Global Health Sector Strategy (GHSS) on Viral Hepatitis to eliminate viral hepatitis as a public health threat by 2030. In pursuit of this elimination goal and recognising that hepatitis control through immunisation is an essential foundation of a hepatitis B prevention programme, the World Health Organization set out vaccine coverage targets for both universal and selective childhood immunisation programmes, focusing on preventing mother to child transmission. In August 2017 the UK introduced a hexavalent (DTaP/IPV/Hib/HepB) combination vaccine into the routine childhood immunisation programme, replacing the pentavalent vaccine given to all infants at 8, 12 and 16 weeks. With the addition of the 6th component to protect against hepatitis B the UK finally introduced universal hepatitis B immunisation. Prior to that, the UK had a selective immunisation policy targeting high risk groups for hepatitis B - including infants born to hepatitis B infected mothers. We tell the story of hepatitis B vaccination in the UK, and how we have evolved from selective to a universal infant immunisation programme, the factors considered in hepatitis B vaccine policy decision-making, and the progress towards elimination of viral hepatitis as a public health threat.